Identification and functional study of the endoplasmic reticulum stress sensor IRE1 in Chlamydomonas reinhardtii. (12th March 2018) - Yamaoka, Yasuyo; Choi, Bae Young; Kim, Hanul; Shin, Seungjun; Kim, Yeongho; Jang, Sunghoon; Song, Won‐Yong; Cho, Chung H.; Yoon, Hwan Su; Kohno, Kenji; Lee, Youngsook
Summary: In many eukaryotes, endoplasmic reticulum (ER) stress activates the unfolded protein response (UPR) via the transmembrane endoribonuclease IRE1 to maintain ER homeostasis. The ER stress response in microalgae has not been studied in detail. Here, we identified Chlamydomonas reinhardtii IRE1 ( CrIRE1 ) and characterized two independent knock‐down alleles of this gene. CrIRE1 is similar to IRE1s identified in budding yeast, plants, and humans, in terms of conserved domains, but differs in having the tandem zinc‐finger domain at the C terminus. CrIRE1 was highly induced under ER stress conditions, and the expression of a chimeric protein consisting of the luminal N‐terminal region of CrIRE1 fused to the cytosolic C‐terminal region of yeast Ire1p rescued the yeast ∆ire1 mutant. Both allelic ire1 knock‐down mutants ire1‐1 and ire1‐2 were much more sensitive than their parental strain CC‐4533 to the ER stress inducers tunicamycin, dithiothreitol and brefeldin A. Treatment with a low concentration of tunicamycin resulted in growth arrest and cytolysis in ire1 mutants, but not in CC‐4533 cells. Furthermore, in the mutants, ER stress marker gene expression was reduced, and reactive oxygen species (ROS) marker gene expression was increased. The survival of ire1 mutants treated with tunicamycin improved in the presence of the ROS scavenger glutathione, suggesting that ire1 mutants failed to maintain ROS levels under ER stress. Together, these results indicate that CrIRE1 functions as an important component of the ER stress response in Chlamydomonas, and suggest that the ER stress sensor IRE1 is highly conserved during the evolutionary history. Significance Statement: Although ER stress responses have been investigated in microalgae, molecular components of the responses remain obscure. Here we identified CrIRE1 as an important factor in the ER stress response in a model microalga Chlamydomonas . CrIRE1 shares conserved domains and alters the expression patterns of ER stress marker genes, similar to other IRE1s, but is unique in its zinc‐finger domain at the C‐terminus. This research provides an insight into the evolution of the ER stress response.